Recent Achievements in the Synthesis of Oxazoles - Duc, Dau X.; Chung, Nguyen Thi (Current Organic Chemistry, 2021)
Oxazole-containing compounds have diverse biological activities, such as antimicrobial, anticancer, antitubercular, antiinflammatory, antidiabetic, antiobesity, antimalarial, and antiviral activities, and some of them have been used as drugs for treating diseases. They also play important roles in the synthesis of bioactive natural products, pharmaceuticals and synthetic transformations as well as in materials, catalyst and agriculture fields. Thus, the development of more efficient and facile synthetic approaches to access oxazole compounds has attracted the intensive interest of chemists, and diverse methods for their synthesis have been investigated. Various established methods have been improved and modified, while numerous novel methods have been discovered. This article will summarize considerable studies on the construction of the oxazole skeleton which date back to 2014.
Keywords: 2-acylamino-ketones